HUBUNGAN KUALITAS PELAYANAN ANC SELAMA PANDEMI COVID-19 DENGAN TINGKAT KEPUASAN IBU HAMIL DI PUSKESMAS URANGAGUNG, SIDOARJO - Nabila Sinta Devi; Diadjeng Setya Wardani; Fatmawati Fatmawati (Journal of Issues in Midwifery, 2023)
Background : Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARSCoV-2 which can attack anyone, including pregnant women. During the Covid-19 pandemic, health services need to carry out routine antenatal care planning that remains of high quality with new policies in order to reduce MMR in Indonesia. Quality ANC services can be measured through the satisfaction of pregnant women. Aims: to determine the relationship between the quality of ANC services with the level of satisfaction of pregnant women at the Urangangung Health Center, Sidoarjo. Method: using analytical observational design with cross sectional approach and analysis using Chi Square method. This study used a sample of 86 pregnant women who underwent ANC examination in August 2021 at the Urangagung Health Center, Sidoarjo. Results: showed that there was no significant relationship between the quality of ANC services during the covid-19 pandemic and the level of satisfaction of pregnant women with a p value of 0.735 > (0.05) and a correlation number of 0.036 including the very weak category. Conclusion: the level of satisfaction obtained by pregnant women at the Urangagung Health Center is not related to the quality of ANC services provided during the Covid-19 pandemic.